2022
DOI: 10.3389/fnins.2021.764342
|View full text |Cite
|
Sign up to set email alerts
|

Musical Sophistication and Speech Auditory-Motor Coupling: Easy Tests for Quick Answers

Abstract: Musical training enhances auditory-motor cortex coupling, which in turn facilitates music and speech perception. How tightly the temporal processing of music and speech are intertwined is a topic of current research. We investigated the relationship between musical sophistication (Goldsmiths Musical Sophistication index, Gold-MSI) and spontaneous speech-to-speech synchronization behavior as an indirect measure of speech auditory-motor cortex coupling strength. In a group of participants (n = 196), we tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…HS speakers synchronize their speech to an external rhythm, whereas LS speakers do not (Assaneo et al, 2019). Also consistent with findings from the general population (Rimmele et al, 2022), we found that differences in synchronization were related to musical training: HS individuals demonstrated more years of musical training than LS individuals. Interestingly, there were no differences between stutterers and non-stutterers on speech-specific SMS based on the SSS test, which is in line with Max and Yudman (2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…HS speakers synchronize their speech to an external rhythm, whereas LS speakers do not (Assaneo et al, 2019). Also consistent with findings from the general population (Rimmele et al, 2022), we found that differences in synchronization were related to musical training: HS individuals demonstrated more years of musical training than LS individuals. Interestingly, there were no differences between stutterers and non-stutterers on speech-specific SMS based on the SSS test, which is in line with Max and Yudman (2003).…”
Section: Discussionsupporting
confidence: 89%
“…Years of musical training is one of the items of the subscale and was the parameter explored in this study. Previous work shows that, in the general population, music experience differs between HS and LS, with the former displaying more years of musical training overall (Assaneo et al, 2019;Rimmele et al, 2022). In addition, musical training is related to the microstructural properties of white matter tracts connecting auditory to motor regions, including the arcuate fasciculus (Halwani et al, 2011), such that HS and LS exhibit differences in this white matter tract (Assaneo et al, 2019).…”
Section: Sss-testmentioning
confidence: 99%
“…The authors reported that auditory-motor synchronization is characterized by a bimodal distribution in the population, classifying individuals into high versus low synchronizers. (The rejection of unimodality has been previously shown with large sample sizes(40, see also:,46). ) Importantly, in addition to superior behavioral synchronization, high synchronizers have stronger structural and functional connectivity between auditory and speech motor cortices (see 40,Figure 3A and B).…”
Section: Introductionmentioning
confidence: 76%
“…indicating an association between musical sophistication and synchronization at fast rates in the speech domain (Rimmele et al, 2022).…”
Section: Synchronization At Different Time Scalesmentioning
confidence: 99%